Dynamic preferential allocation to arbuscular mycorrhizal fungi explains fungal succession and coexistence. Issue 2 (20th December 2017) - Bachelot, Benedicte; Lee, Charlotte T.
Abstract: Evidence accumulates about the role of arbuscular mycorrhizal (AM) fungi in shaping plant communities, but little is known about the factors determining the biomass and coexistence of several types of AM fungi in a plant community. Here, using a consumer‐resource framework that treats the relationship between plants and fungi as simultaneous, reciprocal exploitation, we investigated what patterns of dynamic preferential plant carbon allocation to empirically‐defined fungal types (on‐going partner choice) would be optimal for plants, and how these patterns depend on successional dynamics. We found that ruderal AM fungi can dominate under low steady‐state nutrient availability, and competitor AM fungi can dominate at higher steady‐state nutrient availability; these are conditions characteristic of early and late succession, respectively. We also found that dynamic preferential allocation alone can maintain a diversity of mutualists, suggesting that on‐going partner choice is a new coexistence mechanism for mutualists. Our model can therefore explain both mutualist coexistence and successional strategy, providing a powerful tool to derive testable predictions.